Sie sind auf Seite 1von 4

−𝑏 ± 𝑏 − 4𝑎𝑐 −(−3) ± (−3) −4(1)(2)

𝑓 𝑥 = 𝑓 𝑥 =
2𝑎 2(1)
3± 9−8 3±1
𝑓 𝑥 = 𝑓 𝑥 =
2 2
4 2
𝑓 𝑥 = =2 𝑓 𝑥 = =1
f(x)={ x|x Є N ; -∞ < x > ∞ menos el 2 y el 1} 2 2

g(x)={ x|x Є N ; -∞ < x > ∞ } G(x)={ x|x Є N ; -∞ < x > ∞ }

F(t)={ t|t Є N ; -∞ < t > ∞ } h(x)={ x|x Є N ; 0 ≤ x > ∞ menos el 1}


f(x) 7 46 62 3𝑡 − 4𝑡 − 7
7
x 0 -3 5 t

g(x) 4 4 4 4
8
x 4 1/100 -156 (x+4)

G(x) 0 2 𝑡 (𝑥 − 1)
9
x 1 5 (t+1) 𝑥

𝑥
F(x) -1,33 -0,75 0,2222 (𝑥 + 7)
10
x -1 0 5 (x+3)

𝑥+4 𝑢
h(u) 3 0
11 𝑥 (𝑢 − 4)
u 5 -4 x (u-4)

(𝑥 − 4)
H(s) 12 3 4,0833
12 3
s -2 7 0,5 𝑥

4 4
f(x)
13 -1 -8 -17
x 0 1 3 4 5
-1 -0,7 -0,5 -0,3 -0,1

F(x) 3 2,5 2 1,5 1 0,5

14
18 27,38 24,5 32 40,5 50

-1 -0,7 -0,5 -0,3 -0,1


x 0 0,5 1 1,5 2 2,5
3 3,7 3,5 4 4,5 5

𝑓 𝑥 = 3 − 7𝑥
𝑓 𝑥 + ℎ = 3 − 7(𝑥 + ℎ)
𝑓 𝑥 + ℎ = 3 − 7𝑥 + 7ℎ
𝑓 𝑥 = 3 − 7𝑥
𝑓 𝑥 + ℎ − 𝑓(𝑥) 3 − 7 𝑥 + ℎ − (3 − 7𝑥)
=
ℎ ℎ
15
𝑓 𝑥 + ℎ − 𝑓(𝑥) 3 − 7𝑥 + 7ℎ − 3 − 7𝑥
=
ℎ ℎ
𝑓 𝑥 + ℎ − 𝑓(𝑥) 7ℎ
=
ℎ ℎ
𝑓 𝑥 + ℎ − 𝑓(𝑥)
=7

𝑓 𝑥 = 11𝑥 +4
𝑓 𝑥 + ℎ = 11(𝑥 + ℎ) +4
𝑓 𝑥 + ℎ = 11(𝑥 +2𝑥ℎ + ℎ2 ) + 4
𝑓 𝑥 + ℎ = 11𝑥 + 22𝑥ℎ + 11ℎ2 + 4
𝑓 𝑥 = 11𝑥 +4
𝑓 𝑥 + ℎ − 𝑓(𝑥) 11(𝑥 + ℎ)2 +4 − (11𝑥 2 +4 )
=
ℎ ℎ
15 𝑓 𝑥 + ℎ − 𝑓(𝑥) 11(𝑥 2 +2𝑥ℎ + ℎ2 ) + 4 − (11𝑥 2 +4 )
=
ℎ ℎ
𝑓 𝑥 + ℎ − 𝑓(𝑥) 11𝑥 2 + 22𝑥ℎ + 11ℎ2 + 4 − 11𝑥 2 -4
=
ℎ ℎ
𝑓 𝑥 + ℎ − 𝑓(𝑥) 22𝑥ℎ + 11ℎ2
=
ℎ ℎ
𝑓 𝑥 + ℎ − 𝑓(𝑥)
= 22𝑥 + 11ℎ